Application of avian cytokines as immuno-modulating agents. Issue 4 (2nd December 2015) - UMAR, S.; ARIF, M.; SHAH, M.A.A.; MUNIR, M.T.; YAQOOB, M.; AHMED, S.; KHAN, M.I.; YOUNUS, M.; SHAHZAD, M.
Abstract : The restricted use of antibiotics in the poultry sector has greatly enhanced the search for environment-friendly alternatives and complementary therapeutic approaches to manage infectious diseases in poultry. Cytokines, as natural immune-modulators, offer alternatives to conventional chemical-based therapeutics. Cytokine usage is becoming more feasible in poultry due to recent advancements in the field of immunology and vaccination, leading to the identification and cloning of avian cytokine genes. Existing adjuvants for poultry vaccines can have deleterious side-effects on the health and products of poultry and a subsequent reduction in profits. Therefore, alternative adjuvants must be developed to enhance the impact of vaccination. The use of cloned cytokines as adjuvants in poultry is attracting attention after the identification of new cytokine genes in chicken. Hence, cytokines may be used as therapeutics and vaccine adjuvants for enhancing immune response during infection and vaccination. This review focuses on the recent advancements in the application of avian cytokines as therapeutics or vaccine adjuvants.